The quest for paradise : Gardens, past, present and future - Barbieri, Francesco, 1970-; Heim, Julia (New delhi : NIyogi books, 2013)
Invited by the Queen of the Fairies to return to her kingdom and help in the quest for the true heart of happiness, Geronimo soon finds himself on an adventurous journey riding on the wings of a rainbow-colored dragon through seven fantastic lands.
Keywords: Mice -- Fiction; Fairies -- Fiction; Adventure and adventurers -- Fiction